SCALE UP DAN UJI TEKNIS ALAT PENGERING TIPE FLUIDIZED BED [Scale Up and Technical Test of Fluidized Bed Dryer] - -, Suryadi; -, Sukmawaty; Putra, Guyup Mahardhian Dwi (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2017)
The available Fluidized Bed dryer has low drying capacity so it is necessary to increase the dimensions to improve the drying capacity. This study aimed to increased the dimensions of the Fluidized Bed dryer, to determined the drying capacity, and to conducted technical tests. This research was conducted at Power and Agriculture Machinery, Faculty of Food and Agroindustrial Technology, University of Mataram. The method used in this research was experimental method with mathematical approach. The parameters used in this study was the scale parameter and technical test parameters. Scale Up Fluidized Bed dryer was done in the drying chamber which includes the dimensions of the drying chamber and drying capacity. Technical testing included air flow velocity, the minimum fluidization velocity, temperature, drying time and space dryer efficiency. The drying chamber is a cylinder with a diameter of 40 cm, height 200 cm and 0.1256 m2 area of the base. The capacity of the Fluidized Bed dryer before Scale Up was 4 kg and the capacity after Scale Up was 8 kg. The speed of air flow through the drying chamber was 3 m/s. The distribution of temperature during the drying process ranges between 40-50℃ and 50-60℃. According to the research, the more the masses drained, the longer the time required to dry the material. The efficiency of the drying chamber mostly present in the temperature range of 50-60℃ with a value of 94.04%. Keywords: fluidized bed, scale up, technical test ABSTRAK Alat pengering Fluidized Bed yang tersedia memiliki kapasitas pengeringan yang rendah sehingga diperlukan peningkatan ukuran dimensi alat untuk meningkatkan kapasitas pengeringan. Penelitian ini bertujuan untuk meningkatkan ukuran dimensi alat pengering Fluidized Bed, menentukan kapasitas pengeringan dan melakukan uji teknis. Penelitian ini dilakukan di Laboratorium Daya dan Mesin Pertanian Fakultas Teknologi Pangan dan Agroindustri Universitas Mataram. Metode yang digunakan pada penelitian ini adalah metode eksperimental dengan pendekatan matematis. Parameter yang digunakan pada penelitian ini adalah parameter Scale Up dan parameter uji teknis. Scale Up alat pengering Fluidized Bed dilakukan pada bagian ruang pengering yang meliputi dimensi ruang pengering dan kapasitas pengeringan. Uji teknis meliputi kecepatan aliran udara, kecepatan minimum fluidisasi, suhu, waktu pengeringan, dan efisiensi ruang pengering. Ruang pengering berbentuk silinder dengan diameter 40 cm, tinggi 200 cm, dan luas alas 0,1256 m2. Kapasitas alat pengering Fluidized Bed sebelum Scale Up adalah 4 kg dan kapasitas setelah Scale Up sebesar 8 kg. Kecepatan aliran udara yang melewati ruang pengering adalah 3 m/s. Sebaran suhu selama proses pengeringan berkisar antara 40-50℃ dan 50-60℃. Berdasarkan hasil penelitian semakin banyak massa yang dikeringkan semakin lama waktu yang dibutuhkan untuk mengeringkan bahan tersebut. Efisiensi ruang pengering yang paling besar terdapat pada kisaran suhu 50-60℃ dengan nilai 94,04%. Kata kunci: fluidized bed, scale up, uji teknis